2016
DOI: 10.3748/wjg.v22.i14.3879
|View full text |Cite
|
Sign up to set email alerts
|

Case of metachronous bilateral isolated adrenal metastasis from colorectal adenocarcinoma and review of the literature

Abstract: Rarely has a solitary, metachronous bilateral adrenal metastasis of colorectal cancer been reported. We depict a 41-year-old man who underwent sigmoid colon cancer radical surgery followed by adjuvant chemotherapy for a locally ulcerative sigmoid adenocarcinoma with metachronous bilateral adrenal metastasis revealed by a computed tomography scan. Histopathological examination showed adenocarcinoma, compatible with metastasis from the rectal cancer. The level of serum carcinoembryonic antigen had indicative sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
1
8
0
4
Order By: Relevance
“…Serum carcinoembryonic antigen levels are useful indicators of adrenal gland metastasis after colorectomy, which can be confirmed by imaging modalities such as CT, magnetic resonance imaging, and PET-CT. Other indicators of metastasis by CT and PET-CT include a mass >2 cm in size, a mean attenuation of >10 HU, and a maximum standardized uptake value (max) of >3.1. [ 18 , 19 , 21 ] The findings in the present case (diameter, 2.5 cm; standardized uptake value max, 7.30) were consistent with a previous study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Serum carcinoembryonic antigen levels are useful indicators of adrenal gland metastasis after colorectomy, which can be confirmed by imaging modalities such as CT, magnetic resonance imaging, and PET-CT. Other indicators of metastasis by CT and PET-CT include a mass >2 cm in size, a mean attenuation of >10 HU, and a maximum standardized uptake value (max) of >3.1. [ 18 , 19 , 21 ] The findings in the present case (diameter, 2.5 cm; standardized uptake value max, 7.30) were consistent with a previous study.…”
Section: Discussionsupporting
confidence: 93%
“…The spread of adrenal metastasis occurs by arterial, portal venous, or lymphatic routes. [ 19 ] Generally, hematogenous spread is considered as the major route of metastasis of the primary carcinoma to the adrenal gland. [ 19 ] Katayama et al suggested a plausible route for hematogenous metastasis from the primary site to the adrenal gland via the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous evidence suggesting that solitary adrenal metastatic lesions are infrequent, solitary metastasis to the adrenal glands occurred in nearly half of the patients (44.8%) included in this review and more commonly in a metachronous setting. Adrenal metastases can occur via the arterial, portal venous or lymphatic routes 27 . Owing to its rich blood supply, the adrenal glands are a favoured site for metastatic spread and hematogenous spread is considered the major route of primary carcinoma metastasis to the adrenal 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal metastases can occur via the arterial, portal venous or lymphatic routes 27 . Owing to its rich blood supply, the adrenal glands are a favoured site for metastatic spread and hematogenous spread is considered the major route of primary carcinoma metastasis to the adrenal 27 . Adrenal metastasis from colorectal cancers was identified to have occurred more commonly in male patients, with an average age of over 59 years.…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumors with the highest prevalence of adrenal metastases are breast, lung and kidney carcinomas. The incidence of adrenal metastatic lesions from CRC varies from 0.15 to 17.4% according to the literature [ 4 ]. Generally, preoperative diagnosis is difficult because adrenal metastatic lesions are not only asymptomatic but also morphologically resemble the characteristics of adrenal adenomas.…”
Section: Discussionmentioning
confidence: 99%